2012
DOI: 10.1002/etc.1728
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic toxicity of polychlorinated biphenyl 126 to Tigriopus japonicus: Effects on survival, growth, reproduction, and intrinsic rate of population growth

Abstract: The harpacticoid copepod Tigriopus japonicus has a wide geographical distribution and is considered as a suitable model species for the assessment of toxicity of marine pollutants. The aim of the present study was to test the impacts of polychlorinated biphenyl (PCB) 126 (3,3',4,4',5-pentachlorobiphenyl) on the growth, development, and reproduction of T. japonicus in two successive generations. We first quantified the 96-h 50% lethal concentration (2.83 mg/L; all reported concentrations are nominal values), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Similarly, Guo et al (2012) found that the copepod T. japonicus became more sensitive to PCB 126 exposure as generations developed. Together with other studies (Guo et al, 2012;Massarin et al, 2010;Pane et al, 2004), this work highlights that the offspring may become more sensitive to pollutant exposure or that the toxic effects can accumulate with generations.…”
Section: Multigenerational Toxicity Responsementioning
confidence: 94%
See 3 more Smart Citations
“…Similarly, Guo et al (2012) found that the copepod T. japonicus became more sensitive to PCB 126 exposure as generations developed. Together with other studies (Guo et al, 2012;Massarin et al, 2010;Pane et al, 2004), this work highlights that the offspring may become more sensitive to pollutant exposure or that the toxic effects can accumulate with generations.…”
Section: Multigenerational Toxicity Responsementioning
confidence: 94%
“…Similarly, Guo et al (2012) found that the copepod T. japonicus became more sensitive to PCB 126 exposure as generations developed. Together with other studies (Guo et al, 2012;Massarin et al, 2010;Pane et al, 2004), this work highlights that the offspring may become more sensitive to pollutant exposure or that the toxic effects can accumulate with generations. Lee et al (2008) reported that, of the seven traits (nauplius phase, development time, survival, sex ratio, number of clutch, nauplii per clutch, and fecundity), only the length of the nauplius phase and development time in T. japonicus displayed a greater sensitivity to several marine pollutants including copper and arsenic during a two-generation life cycle exposure, which is inconsistent with our study.…”
Section: Multigenerational Toxicity Responsementioning
confidence: 94%
See 2 more Smart Citations
“…This copepod inhabits tide pools on rocky shores along the coasts in the Western Pacific including Japan, South Korea, and China 36 , and thus it may have suffered from multi-stresses (e.g., OA and Hg pollution) due to human activities. We specifically examined the combined effects of OA and Hg on the multigenerational life history of this copepod.…”
Section: Introductionmentioning
confidence: 99%